The Consistory and Social Discipline in Calvin's Geneva - Watt, Jeffrey (Changing Perspectives on Early Modern Europe, 2020)
Created by John Calvin, the Consistory of Geneva was a quasi-tribunal entrusted with enforcing Reformed morality. Comprised of pastors and elders, this body met weekly and summoned people for a wide range of "sinful" behavior, such as drunkenness, dancing, blasphemy, or simply quarrels, and was a far more intrusive institution than the Catholic Inquisition. Among the thousands summoned during Calvin's ministry were a pair of women who were allegedly prophets, boys who skipped catechism to practice martial arts, and a good number of people begging for forgiveness for having renounced Protestantism out of fear of death. This superbly researched book, reflecting author Jeffrey Watt's career-long involvement in the ongoing project of transcribing, editing, and publishing the Consistory records, is the first comprehensive examination of this morals court and provides a window into the reception of the Reformation in the so-called Protestant Rome. Watt examines the role of the Consistory in upholding patriarchy, showing that while Genevan authorities did not have a double standard in prosecuting illicit sexuality, the Consistory exhorted women to obey even violently abusive husbands. He finds also that Calvin and his colleagues vigorously promoted a strong work ethic by censuring people, mostly men, for laziness, and showed a surprising degree of skepticism toward accusations of witchcraft patterns. Finally, Watt demonstrates convincingly that, while the Consistory encountered some resistance, Genevans by and large shared the ideals it promoted and that it enjoyed considerable success in fostering discipline in Genevan society. JEFFREY R. WATT is the Kelly Gene Cook Sr. Professor of History at the University of Mississippi. This book will be made openly available in digital formats thanks to a generous grant from the Andrew W. Mellon Foundation.